2004
DOI: 10.1093/jb/mvh057
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia coli Uridine Phosphorylase by Single-Site Mutagenesis

Abstract: The Escherichia coli udp gene encodes uridine phosphorylase (UP), which catalyzes the reversible phosphorolysis of uridine to uracil and ribose-1-phosphate. The X-ray structure of E. coli UP resolved by two different groups produced conflicting results. In order to cast some light on the E. coli UP catalytic site, we mutagenized several residues in UP and measured by RP-HPLC the phosphorolytic activity of the mutant UP proteins in vitro. Mutations Thr94Ala, Phe162Ala, and Tyr195Gly caused a drastic decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The use of whole cells to synthesis nucleoside analogues has been used increasingly (Rocchietti et al 2004;End and Schoning 2004;Tonon et al 2004), as the isolation and purification of enzymes can be avoided (Oliva et al 2004a;b;Panova et al 2007). More recently, the construction of genetically modified bacteria that express high levels of recombinant NPs have been used successfully in the production of isolated enzymes and as whole cell biocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The use of whole cells to synthesis nucleoside analogues has been used increasingly (Rocchietti et al 2004;End and Schoning 2004;Tonon et al 2004), as the isolation and purification of enzymes can be avoided (Oliva et al 2004a;b;Panova et al 2007). More recently, the construction of genetically modified bacteria that express high levels of recombinant NPs have been used successfully in the production of isolated enzymes and as whole cell biocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of E. coli UP in a complex with substrates was analyzed (see [3940] and the works cited therein) and the role of some amino acid residues of the catalytic site was characterized by the single-site mutagenesis [41]. It was suggested that the uracil binding site includes Gln166, the carboxamide group of which forms two strong hydrogen bonds 3N(H)···(O=)C(R)-NH 2 ···(O=)C-2.…”
Section: Resultsmentioning
confidence: 99%